2005
DOI: 10.1002/chem.200500434
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Intra‐ and Interligand Charge Transfer with Variation of the Axial N‐Heterocyclic Ligand in Osmium(II) Pyridylpyrazolate Complexes: Extensive Color Tuning by Phosphorescent Solvatochromism

Abstract: The rational design and syntheses of a new series of Os(II) complexes with formula [Os(fppz)(2)(CO)(L)] (1: L=4-dimethylaminopyridine; 2: L = pyridine; 3: L = 4,4'-bipyridine; 4: L = pyridazine; 5: L = 4-cyanopyridine), bearing two (2-pyridyl)pyrazolate ligands (fppz) together with one carbonyl and one N-heterocyclic ligand at the axial positions are reported. Single-crystal X-ray diffraction studies of, for example, 2 reveal a distorted octahedral geometry in which both fppz ligands reside in the equatorial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 52 publications
2
8
1
Order By: Relevance
“…Thus, this emission can be described as originating from 3 {[d yz (Ru) + π(fppz)] [π*(L)]} excited state with the 3 MLCT/ 3 LLCT character (Figure 4(b)). Our calculated results agree with the variation trend of the corresponding Os complexes obtained by Chou et al [21] .…”
Section: Emissionssupporting
confidence: 94%
See 2 more Smart Citations
“…Thus, this emission can be described as originating from 3 {[d yz (Ru) + π(fppz)] [π*(L)]} excited state with the 3 MLCT/ 3 LLCT character (Figure 4(b)). Our calculated results agree with the variation trend of the corresponding Os complexes obtained by Chou et al [21] .…”
Section: Emissionssupporting
confidence: 94%
“…The frontier molecular orbital energy levels of 1−3 in vacuo, C 6 H 12 , and CH 3 CN media are given in Table 9. For complexes 1 and 2, Tables 8 and 9 show that there is little solvent effect on the energy levels of frontier molecular orbital (∆E < 0.25 eV), the excitation energy of the lowest-lying absorption (∆E < 0.23 eV) and the emission (∆E < 0.08 eV), which is consistent with the experimental trends obtained by Chou et al [21] . The calculation results also showed that there is a little blue-shift in the absorption and the emission spectra of 1 and 2 along with the increase of the solvent polarity in vacuo, C 6 H 12 , and CH 3 CN media.…”
Section: Solvatochromismsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, treatment of complex 20 with a nitrogen donor ligand led to the formation of a new series of Os II complexes with formula [Os(fppz) 2 (CO)(L)] ( 23 , L = 4‐dimethylaminopyridine; 24 , L = pyridine; 25 , L = 4,4′‐bipyridine; 26 , L = pyridazine; 27 , L = 4‐cyanopyridine); the remaining carbonyl ligands and the N‐heterocyclic ligand are located at the axial positions 34. Variation in the axial N‐heterocyclic ligand leads to remarkable changes in photophysical properties such that the energy gap and the phosphorescence peak wavelength can be fine‐tuned.…”
Section: [Os(co)2] Derivativesmentioning
confidence: 99%
“…In order to accomplish our goal, we have designed two Os­(II)–terpyridine complexes based on a bifunctional terpyridine–bipyridine ligand, dipy-Hbzim-tpy, and thoroughly studied their stimuli-responsive photophysical properties (Chart ). Although a sizeable number of reports on polypyridyl Os­(II) complexes exhibiting NIR luminescence are available in the literature from our laboratory as well as from other research groups, but to our knowledge, there is no report wherein the optical as well as NIR luminescence properties of bis-terpyridine Os­(II) complexes were tuned and/or switched simultaneously upon interaction with anions, cations, pH, protons, and solvents.…”
Section: Introductionmentioning
confidence: 99%